2017
DOI: 10.1021/acs.chemrev.7b00353
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Flow Microreactors in Electrosynthetic Processes

Abstract: The fundamental advantages and potential benefits of flow microreactor technology include extremely large surface-to-volume ratios, precise control over temperature and residence time, extremely fast molecular diffusion, and increased safety during reactive processes. These advantages and benefits can be applied to a wide range of electrosynthetic techniques, and so the integration of flow microreactors with electrosynthesis has received significant research interest from both academia and industry. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
185
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(189 citation statements)
references
References 132 publications
1
185
0
3
Order By: Relevance
“…[3] Organic electrochemistry is ap owerful method for organic synthesis,b ut there are also limitations for electrochemistry in batch processes.A sc ommon organic solvents have typically low conductivity,t he use and subsequent removal of supporting electrolytes is necessary.T he large distance between electrodes in batch processes leads to large current gradients.Continuous flow reactors can address some of these problems. [4] Small electrode distances avoid large current gradients and reactions can be performed with small amounts or even without addition of supporting electrolytes, although modification of electrode surfaces has also been investigated. [5] Ah igh electrode surface-to-reactor volume ratio allows amuch improved mass transfer on the surface of the electrodes leading to milder reaction conditions and short reaction times.…”
mentioning
confidence: 99%
“…[3] Organic electrochemistry is ap owerful method for organic synthesis,b ut there are also limitations for electrochemistry in batch processes.A sc ommon organic solvents have typically low conductivity,t he use and subsequent removal of supporting electrolytes is necessary.T he large distance between electrodes in batch processes leads to large current gradients.Continuous flow reactors can address some of these problems. [4] Small electrode distances avoid large current gradients and reactions can be performed with small amounts or even without addition of supporting electrolytes, although modification of electrode surfaces has also been investigated. [5] Ah igh electrode surface-to-reactor volume ratio allows amuch improved mass transfer on the surface of the electrodes leading to milder reaction conditions and short reaction times.…”
mentioning
confidence: 99%
“…Biphasic reaction conditions (acetonitrile/1 M HCl) are required and the reaction was carried out in batch. However, preliminary studies showed that the use of flow chemistry was of great benefit [16][17][18][19][20]. The reaction time could be reduced to the minute range in flow and no mass transfer limitations were observed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, flow electrochemistry offers many advantageso ver batch electrochemistry. [18,[36][37][38][39][40][41][42][43] For example, al arge ratio of electrode surface to reactor volume reduces the reaction time. In addition, the short distance between electrodes enables am ore efficient mass transfer and allows the use of low concentrations of supporting electrolyte or even no supporting electrolyte at all.…”
Section: Introductionmentioning
confidence: 99%